McFarland, USA [videorecording (DVD)] - Rodríguez, Ramiro, 1966-; Costner, Kevin; Pratts, Carlos, 1986- (Disney, 2015)
Inspired by the 1987 true story, the movie follows novice runners from McFarland, an economically challenged town in California's farm-rich Central Valley, as they give their all to build a cross-country team under the direction of Coach Jim White, a newcomer to their predominantly Latino high school. With grit and determination, the unlikely band of runners eventually overcomes the odds to forge not only a championship cross-country team but an enduring legacy as well.